1980
DOI: 10.1073/pnas.77.10.5989
|View full text |Cite
|
Sign up to set email alerts
|

Purification of kidney epithelial cell growth inhibitors.

Abstract: Two high molecular weight growth inhibitors have been isolated from the culture medium of BSC-1 cells, epithelial cells of African green monkey kidney. The purified kidney epithelial cell growth inhibitors, at ng/ml concentrations, reversibly arrest the growth of BSC-1 cells in the GI phase of the cell cycle. Their action is selective; they are most active on BSC-1 cells, are less active as inhibitors of the growth of rat lung and human breast epithelial cells, and do not inhibit the growth of 3T3 mouse embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(74 citation statements)
references
References 22 publications
1
71
0
2
Order By: Relevance
“…4, compo In addition, it would be of obvious interest to establish the relationship between the Mr 13,000 polypeptide in FGR-s and similar growth-inhibitory activities reported in other systems. These include (i) the membrane-bound growth-inhibitory activities of 3T3 cells reported by Glaser (13,14), Peterson (15,16), and Datta (17,18) and their co-workers; (ii) the highly purified growth-inhibitory factor from medium of BSC-1 cells (19,20); (iii) the hepatic proliferation inhibitor (Mr, 26,000; pI, 4.65) isolated from normal rat livers (21,22); and (iv) the growth-inhibitory glycopeptides identified and partially purified from mouse and bovine cerebral cortex cells (23,24). More recently, it has been shown that secondary cultures of mouse embryo fibroblasts release into the medium a growth-inhibitory activity whose physicochemical behavior closely parallels that of FGR-s (25) and that a growth inhibitor for Ehrlich ascites mammary carcinoma cells can be isolated from the bovine mammary gland (26).…”
Section: Discussionmentioning
confidence: 99%
“…4, compo In addition, it would be of obvious interest to establish the relationship between the Mr 13,000 polypeptide in FGR-s and similar growth-inhibitory activities reported in other systems. These include (i) the membrane-bound growth-inhibitory activities of 3T3 cells reported by Glaser (13,14), Peterson (15,16), and Datta (17,18) and their co-workers; (ii) the highly purified growth-inhibitory factor from medium of BSC-1 cells (19,20); (iii) the hepatic proliferation inhibitor (Mr, 26,000; pI, 4.65) isolated from normal rat livers (21,22); and (iv) the growth-inhibitory glycopeptides identified and partially purified from mouse and bovine cerebral cortex cells (23,24). More recently, it has been shown that secondary cultures of mouse embryo fibroblasts release into the medium a growth-inhibitory activity whose physicochemical behavior closely parallels that of FGR-s (25) and that a growth inhibitor for Ehrlich ascites mammary carcinoma cells can be isolated from the bovine mammary gland (26).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, little is known about the role of growth inhibitory factors, although they clearly are involved in the control of cell proliferation which itself is critical in the carcinogenic process as discussed in depth by Potter (4,5). Considerable literature is available on the existence ofinhibitors ofcell proliferation in different cells and tissues (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), but such factors from normal tissues have not been purified.…”
mentioning
confidence: 99%
“…Unlike fibroblasts, many epithelial cell types will not grow in high concentrations of serum, perhaps owing to the presence of one or more inhibitory factors (2,12, 20). Although some oncogenic viruses have been useful for the transformation of specific differentiated cell types in vitro, such as the transformation of pre-B cells by Abelson virus (34), no viruses have been consistently successful in the transformation of diverse epithelial cells (33).…”
mentioning
confidence: 99%